Dispensing errors in Lebanese community pharmacies: incidence, types, underlying causes, and associated factors - Lama Soubra; Samar Karout (Pharmacy Practice, 2021)
Objectives: To assess the incidence, types, the causes of as well as the factors associated with dispensing errors in community pharmacies in Lebanon.